2023
DOI: 10.1155/2023/1945290
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Using Weighted Blankets among Children with ADHD and Sleeping Difficulties

Abstract: Introduction. Sleeping difficulties are common in children with attention deficit hyperactivity disorder (ADHD). A sleep intervention with weighted blankets was designed to increase current understanding of using weighted blankets to target children’s individual needs in connection with sleep and daytime functioning. Aim. To explore how children with ADHD and sleeping difficulties experience the use of weighted blankets. Methods. An explorative qualitative design in which 26 children with ADHD and sleeping dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Improved child and family functioning when using WBs was confirmed in interviews with children (Lönn et al, 2023) and parents (Larsson et al, 2021).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Improved child and family functioning when using WBs was confirmed in interviews with children (Lönn et al, 2023) and parents (Larsson et al, 2021).…”
Section: Discussionmentioning
confidence: 80%
“…If children's restlessness and subsequent sleep problems decrease during night‐time, the whole family may experience improved functioning and overall well‐being. Improved child and family functioning when using WBs was confirmed in interviews with children (Lönn et al, 2023) and parents (Larsson et al, 2021).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Similarly, A qualitative study based on parents’ experiences of the impact of weighted blankets on children with ADHD and sleep disorders indicated that after 16 weeks of weighted blankets intervention, children could better master everyday life, and achieve satisfactory sleep and overall well-being ( 31 ). Another qualitative study based on children’s experiences revealed that the use of weighted blankets improved the emotional regulation, everyday participation and sleep quality of children with ADHD and sleeping difficulties ( 33 ). Moreover, in Idaho, USA, a single-subject design study ( 28 ) and two continuation studies ( 15 , 29 ) in children with ASD and sleep disorders indicated that weighted blankets were beneficial for the improvement of overall sleep quality, especially the sleep onset latency, awakening times, sleep duration, and morning mood, although the effects were not sufficient to recommend for clinical use.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that weighted blankets can be dangerous, especially for children and the elderly. The higher weight of weighted blankets may cause pain, anxiety, and panic to a few children ( 33 , 73 ). In general, children under 3 years of age or weighing less than 50 pounds should not use weighted blankets due to the risk of suffocation or entrapment.…”
Section: Discussionmentioning
confidence: 99%